Influence of exposure to coarse, fine and ultrafine urban particulate matter and their biological constituents on neural biomarkers in a randomized controlled crossover study. (April 2017) - Liu, Ling; Urch, Bruce; Szyszkowicz, Mieczyslaw; Speck, Mary; Leingartner, Karen; Shutt, Robin; Pelletier, Guillaume; Gold, Diane R.; Scott, James A.; Brook, Jeffrey R.; Thorne, Peter S.; Silverman, Frances S.
Abstract: Background: Epidemiological studies have reported associations between air pollution and neuro-psychological conditions. Biological mechanisms behind these findings are still not clear. Objectives: We examined changes in blood and urinary neural biomarkers following exposure to concentrated ambient coarse, fine and ultrafine particles. Methods: Fifty healthy non-smoking volunteers, mean age 28 years, were exposed to coarse (2.5–10 μm, mean 213 μg/m 3 ) and fine (0.15–2.5 μm, mean 238 μg/m 3 ) concentrated ambient particles (CAPs), and filtered ambient and/or medical air. Twenty-five participants were exposed to ultrafine CAP (mean size 59.6 nm, range 47.0–69.8 nm), mean (136 μg/m 3 ) and filtered medical air. Exposures lasted 130 min, separated by ≥ 2 weeks, and the biological constituents endotoxin and β-1, 3-d -glucan of each particle size fraction were measured. Blood and urine samples were collected pre-exposure, and 1-hour and 21-hour post-exposure to determine neural biomarker levels. Mixed-model regressions assessed associations between exposures and changes in biomarker levels. Results: Results were expressed as percent change from daily pre-exposure biomarker levels. Exposure to coarse CAP was significantly associated with increased urinary levels of the stress-related biomarkers vanillylmandelic acid (VMA) and cortisol when compared with exposure to filtered medical air [20% (95% confidence interval: 1.0%, 38%) and 64% (0.2%, 127%), respectively] 21 hours post-exposure. However exposure to coarse CAP was significantly associated with decreases in blood cortisol [− 26.0% (− 42.4%, − 9.6%) and − 22.4% (− 43.7%, − 1.1%) at 1 h and 21 h post-exposure, respectively]. Biological molecules present in coarse CAP were significantly associated with blood biomarkers indicative of blood brain barrier integrity. Endotoxin content was significantly associated with increased blood ubiquitin C-terminal hydrolase L1 [UCHL1, 11% (5.3%, 16%) per ln(ng/m 3 + 1)] 1-hour post-exposure, while β-1, 3-d -glucan was significantly associated with increased blood S100B [6.3% (3.2%, 9.4%) per ln(ng/m 3 + 1)], as well as UCHL1 [3.1% (0.4%, 5.9%) per ln(ng/m 3 + 1)], one-hour post-exposure. Fine CAP was marginally associated with increased blood UCHL1 when compared with exposure to filtered medical air [17.7% (− 1.7%, 37.2%), p = 0.07] 21 hours post-exposure. Ultrafine CAP was not significantly associated with changes in any blood and urinary neural biomarkers examined. Conclusion: Ambient coarse particulate matter and its biological constituents may influence neural biomarker levels that reflect perturbations of blood-brain barrier integrity and systemic stress response. Highlights: Healthy volunteers were exposed to filtered clean air, and coarse, fine and ultrafine particles coming from outdoor air. Endotoxin and β-1, 3-D-glucan in the particles, and neural biomarker levels in blood and urine were measured. Associations between exposure to particulate matter and changes in neural biomarkers were examined. Coarse particles and its biological constituents may influence perturbations of blood-brain barrier and systemic stress.